Impact of the COVID-19 Pandemic on Mental Health Law in the State of Qatar - Majid Alabdulla (12051430) (2021)
Accumulating evidence exploring the impact of the pandemic on mental health has been published as the Covid-19 pandemic has evolved and reflect how shock, anxiety, and fear of the early periods of the pandemic are giving way to depression and PTSD symptoms as the pandemic and its restrictions persist (Thombs et al., 2020; Vindegaard & Benros, 2020). The general findings have been those of increased psychiatric morbidity in general populations, psychiatric populations, and special groups like quarantined and isolated populations (Reagu et al., 2021; Salari, Hosseinian-Far, Jalali, et al., 2020). Other Information Published in: International Journal of Law and Psychiatry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijlp.2021.101748